2016
DOI: 10.5430/jha.v5n5p60
|View full text |Cite
|
Sign up to set email alerts
|

A quality improvement project to reduce intravenous catheter related infections in the neonatology unit of Kibogora hospital in Rwanda

Abstract: In developing countries, intravenous (IV) catheter related infections (CRI) rate is generally high. Neonates are more susceptible to develop CRI. We examined the impact of a quality improvement project on IV CRI rates in the neonatal intensive care unit (NICU) of a district hospital in Rwanda. A pre-and post-intervention study was conducted from 2014 to 2016 to evaluate the IV CRI rate and nurses' IV management technique. A written test was administered to evaluate their knowledge on the matter. The interventi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 23 publications
(31 reference statements)
0
5
0
Order By: Relevance
“…Previous data have shown that adverse outcomes during vascular access and central venous catheter placement, such as infection, thrombosis, inadvertent puncture of adjacent vasculature, and vessel injury, are associated with provider experience, multiple access attempts and needle repositions [23][24][25] . Certainly, the adoption of U/S over landmark technique has improved rates of successful vascular J o u r n a l P r e -p r o o f access by 14-29%, and reduced inadvertent vascular puncture by 7.7% 26 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous data have shown that adverse outcomes during vascular access and central venous catheter placement, such as infection, thrombosis, inadvertent puncture of adjacent vasculature, and vessel injury, are associated with provider experience, multiple access attempts and needle repositions [23][24][25] . Certainly, the adoption of U/S over landmark technique has improved rates of successful vascular J o u r n a l P r e -p r o o f access by 14-29%, and reduced inadvertent vascular puncture by 7.7% 26 .…”
Section: Discussionmentioning
confidence: 99%
“…Previous data have shown that adverse outcomes during vascular access and central venous catheter placement, such as infection, thrombosis, inadvertent puncture of adjacent vasculature, and vessel injury, are associated with provider experience, multiple access attempts, and needle repositions. 23 , 24 , 25 The adoption of US over landmark technique has improved rates of successful vascular access by 14%–29% and reduced inadvertent vascular puncture by 7.7%. 26 Data from the GUIDE study show that MantUS further improved the users’ ability to obtain vascular access compared to conventional US, showing statistical significance for reduction of needle repositions.…”
Section: Discussionmentioning
confidence: 99%
“…Repeated needle-insertion attempts cause patient discomfort and decrease patient satisfaction 6 , 10 ; they lead to venous depletion and increase infection risk. 8 An improvement in first-insertion success thus reduced cost by minimizing increased expenditure associated with these negative outcomes. Better first-attempt success rates were also associated with greater ease of vascular access and improved efficiency for health care workers, which resulted in higher health care worker satisfaction.…”
Section: Discussionmentioning
confidence: 99%
“… 7 Repeated needle-insertion attempts may cause patient psychological complications, such as distress and anxiety, as well as pain, vein injury, and enhanced risk of infection. 5 , 6 , 8 10 They may also contribute negatively to patient satisfaction. 6 In more controlled settings with specialized intravenous (IV) catheter teams and implementation of process improvement programs, success rates can be improved.…”
mentioning
confidence: 99%
“…[11] The SPS framework has been used in many health care organizations and the methodology has shown to be particularly effective in resource-limited settings. [12][13][14][15][16] The eight steps of SPS approach are: 1) defining the problem; 2) setting an objective; 3) conducting a root cause analysis; 4) generating alternative strategies; 5) comparing strategies; 6) selecting a strategy; 7) implementing the strategy; and 8) evaluating its impact on the problem. [17] This quality improvement project followed the SPS 8-step approach to address the delay in the starting of first surgeries in one of the referral hospitals in Kigali, Rwanda.…”
Section: Introductionmentioning
confidence: 99%